2022
DOI: 10.1371/journal.pntd.0010261
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition, anemia, micronutrient deficiency and parasitic infections among schoolchildren in rural Tanzania

Abstract: Background Malnutrition, anemia, micronutrient deficiency and parasitic infections continue to impact the nutritional status and health of children in lower-income countries, however not enough data concerning this issue is available. The aim of this study was to assess the distribution of nutritional indicators, anemia and micronutrient deficiency and their underlying risk factors among schoolchildren in south-eastern Tanzania. Method/Principal findings This cross-sectional study enrolled primary schoolchil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Boys were more likely to be anemic than girls, which was consistent with previous studies in Ethiopia (Melku et al, 2018), Togo (Nambiema et al, 2019), and in Boricha Woreda, Southern Ethiopia (Yoseph & Beyene, 2020). The ZDHS 2015 indicated a small variation by gender (38% of boys were anemic compared with 36% of girls) while other studies in rural Tanzania have found the opposite (Mrimi et al, 2022). The higher prevalence in boys could be related to the higher growth rate in boys resulting in a greater need for iron by the body, which might not be met by the diet (Silla et al, 2013).…”
Section: Predictors Of Anemia In Children 6-59 Months Old (Model 1)mentioning
confidence: 95%
See 1 more Smart Citation
“…Boys were more likely to be anemic than girls, which was consistent with previous studies in Ethiopia (Melku et al, 2018), Togo (Nambiema et al, 2019), and in Boricha Woreda, Southern Ethiopia (Yoseph & Beyene, 2020). The ZDHS 2015 indicated a small variation by gender (38% of boys were anemic compared with 36% of girls) while other studies in rural Tanzania have found the opposite (Mrimi et al, 2022). The higher prevalence in boys could be related to the higher growth rate in boys resulting in a greater need for iron by the body, which might not be met by the diet (Silla et al, 2013).…”
Section: Predictors Of Anemia In Children 6-59 Months Old (Model 1)mentioning
confidence: 95%
“…Anemia is often associated with multiple proximal risk factors (iron and vitamin A deficiencies, inflammation, malaria, age, gender, and body mass index [BMI]) and distal risk factors (education status, sanitation and hygiene facilities, and urban or rural residence) (Cane et al, 2022; Mrimi et al, 2022; Wirth et al, 2017). In Zimbabwe, the major causes of anemia in children and WRA are likely to include malaria, helminths, iron, and other nutritional deficiencies and chronic infections (ZIMSTAT, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we conducted a cross-sectional survey with schoolchildren living in rural south-eastern Tanzania. Our findings on the prevalence of parasitic infections, undernutrition, micronutrient deficiency and demography have been published elsewhere [15,16]. The aim of the current study was to correlate the concentration of cytokines IL-4, IFNγ and interleukin 17A (IL-17A) with: (i) the presence or absence of parasitic infections, clinical signs and symptoms, undernutrition, anaemia, micronutrient deficiency, inflammatory and anaemia markers, and (ii) household and community risk factors such as drinking water sources and sanitation, housing quality, location of the school and socioeconomic status, which play a role in parasite transmission and infection.…”
Section: Introductionmentioning
confidence: 92%
“…Micronutrient malnutrition has a direct impact on the overall health. More than two billion people in the world today may be affected by micronutrient malnutrition (14). Vitamin A deficiency, iron deficiency anemia, and iodine deficiency disorders are the most common forms of micronutrient malnutrition (15).…”
Section: Introductionmentioning
confidence: 99%